Recruiting Chinese Americans into Cancer Screening Intervention Trials: Strategies and Outcomes - Wang, Judy Huei-yu (2014)
BACKGROUND: Cancer is the leading cause of death among Asian Americans. While Asian Americans are the fastest growing minority population in the United States, they are under-represented in cancer research and report poor adherence to cancer screening guidelines. PURPOSE: This study utilized data from two large randomized intervention trials to evaluate strategies to recruit first-generation Chinese American immigrants from community settings and Chinese American physician practices. Findings will inform effective strategies for promoting Asian American participation in cancer control research. METHODS: Chinese Americans who were nonadherent to annual mammography screening guidelines (Study 1 with 664 immigrant women >age 40) and to colorectal cancer screening guidelines (Study 2 with 455 immigrants >age 50) were enrolled from the greater Washington DC, New York City (NYC), and Philadelphia (PA) areas. Both studies trained bilingual staff to enroll Chinese-speaking participants with the aid of linguistically appropriate fliers and brochures to obtain consent. Study 1 adopted community approaches and worked with community organizations to enroll participants. Study 2 randomly selected potential participants through 24 Chinese American primary care physician offices, and mailed letters from physicians to enroll patients, followed by telephone calls from research staff. The success of recruitment approaches was assessed by yield rates based on number of participants approached, ineligible, and consented. RESULTS: Most participants (70%) of Study 1 were enrolled through in-person community approaches (e.g, Chinese schools, stores, health fairs, and personal networks). The final yield of specific venues differed widely (6% to 100%) due to various proportions of ineligible subjects (2% to 64%) and refusals (0% to 92%). The Study 2 recruitment approach (physician letter followed by telephone calls) had different outcomes in two geographic areas, partially due to differences in demographic characteristics in the DC and NYC/PA areas. The community approaches enrolled more recent immigrants and uninsured Chinese Americans than the physician and telephone call approach (p<.001). Enrollment cost is provided to inform future research studies. LIMITATIONS: Our recruitment outcomes might not be generalizable to all Chinese Americans or other Asian American populations because they may vary by study protocols (e.g., length of trials), target populations (i.e., eligibility criteria), and available resources. CONCLUSIONS: Use of multiple culturally relevant strategies (e.g., building trusting relationships through face-to-face enrollment, use of bilingual and bicultural staff, use of a physician letter, and employing linguistically appropriate materials) was crucial for successfully recruiting a large number of Chinese Americans in community and clinical settings. Our data demonstrates that substantial effort is required for recruitment; studies need to budget for this effort to ensure the inclusion of Asian Americans in health research.